Peningkatan Hasil Belajar Siswa pada Materi Lebih Dekat Dengan Nama-Nama Allah Melalui Strategi Pembelajaran The Firing Line Siswa Kelas V SDN 118 Kaur - Ade Afriansah (GHAITSA : Islamic Education Journal, 2025)
This study aims to determine whether The Firing Line learning strategy can improve the learning outcomes of fifth grade students of SDN 118 Kaur. This study was conducted in three cycles and each cycle was conducted in two meetings. In order for this classroom action research to be successful without obstacles that interfere with the smoothness of the research, the researcher compiled the stages that were passed through in the classroom action research, namely: 1) Planning/preparation of action, 2) Implementation of action, 3) Observation, and Reflection. The results of the study indicate that through the application of The Firing Line learning strategy, learning outcomes in Islamic Religious Education (PAI) lessons for fifth grade students of SDN 118 Kaur can be improved, this can be proven by the increase in learning outcomes before the action was carried out in cycle I and cycle II and cycle III. Before the action was carried out, student learning outcomes were classified as lacking with an average of 49.0%, there was an increase in cycle I with an average of 62.3%. While student learning outcomes in cycle II also increased with an average of 73.7% with a good category, in cycle III there was an increase with an average of 90.1% with a good category, this proves that with The Firing Line learning strategy can improve the learning outcomes of class V students of SDN 118 Kaur. The student learning outcomes obtained in cycle III, it can be seen that the student learning outcomes have reached the success criteria, which is 75%.